2013
DOI: 10.1186/1475-2891-12-35
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peanut and grain bar preloads on postmeal satiety, glycemia, and weight loss in healthy individuals: an acute and a chronic randomized intervention trial

Abstract: BackgroundPeanut consumption favorably influences satiety. This study examined the acute effect of peanut versus grain bar preloads on postmeal satiety and glycemia in healthy adults and the long-term effect of these meal preloads on body mass in healthy overweight adults.MethodsIn the acute crossover trial (n = 15; 28.4 ± 2.9 y; 23.1 ± 0.9 kg/m2), the preload (isoenergetic peanut or grain bar with water, or water alone) was followed after 60 min with ingestion of a standardized glycemic test meal. Satiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…The first is that peanuts hold high satiety value since they are a rich source of fiber and protein (1,20,21). In this trial, there were no significant differences in appetitive ratings between groups.…”
Section: Obesitymentioning
confidence: 67%
See 4 more Smart Citations
“…The first is that peanuts hold high satiety value since they are a rich source of fiber and protein (1,20,21). In this trial, there were no significant differences in appetitive ratings between groups.…”
Section: Obesitymentioning
confidence: 67%
“…In this trial, there were no significant differences in appetitive ratings between groups. A recent study reported that conventional peanut consumption lead to greater satiety compared to control treatment after 1 h of its intake (21). Given the groups consuming peanuts ingested less energy, this suggests the inclusion of peanuts in the diet did enhance satiety.…”
Section: Obesitymentioning
confidence: 98%
See 3 more Smart Citations